Suicide ideation among Sudanese adults cross in Khartoum state Sudan - Ibrahim, Radwa Mohamad; Alsharif, Fath-Alrhman Omer; Omara, Nadir Elzain (Journal of Educational and Psychological Sciences, 2025)
Worldwide suicidal behaviors are not uncommon among adults, in Sudan; there is a lack of published data on suicidal behaviors. Yet, no studies to date have examined the prevalence of and risk factors for suicide ideation, plans, and attempts, in the general population. This study aimed to explore the prevalence and the possible risk factors of suicide ideation among Sudanese adults aged18-35 and to compare the difference in suicide ideation risk factors between young and older adults .A total of 394 adults were participate dither study, but only 284 first participants were included, socio demographic data, suicidal behaviors,datafrom5-item Brief Symptom Rating Subscale (BSRS- 5),and possible risk factors data were collected using online self-administered questionnaire. Suicidal ideation prevalence was reported by 27.1% of the study population sample. Suicidal ideation was more prevalent in females. 6.5% of the participants had one suicidal attempt during the past 12 months and 5.7% of the participants reported more than one suicidal attempt, results showed that family problems, relationship problems, previous sexual assault, and the presence of mental illness are associated with suicidal ideation among adults. The results provide valuable information about Suicidal behaviors and risk factors associated with suicidal ideation among Sudanese adults, more studies regarding suicidal behaviors among adults as they represent society’s back bone should be performed to set prevention programs and raise awareness about mental health.